A new species of Zosime (Copepoda: Harpacticoida: Zosimeidae) from shallow subtidal habitats in Korea, with notes on the genus - Kim, Jong Guk; Jung, Tae Won; Yoon, Seong Myeong (Zootaxa, 2016)
Zosime destituta sp. nov. is described from shallow subtidal habitats in the southern sea of Korea. The new species is similar to Z. valida Sars, 1919, but differs from it primarily by the lack of an inner seta on the third endopodal segment of the fourth swimming leg. Based on morphological comparison of female character states, the genus Zosime can be subdivided into three provisional groups, anneae-, incrassata-, and typica-group. These groups are distinguished from each other by differences in the antennule, antennary exopod, mandibular rami, armature of swimming legs, fifth leg, and caudal rami. In addition, Zosime incrassata bathybia Bodin, 1968 is removed from its synonymy with Z. incrassata Sars, 1910 and upgraded to species level. An amended key to all known species of Zosime Boeck, 1873 is given, along with a table of all major characters. The present study is the first report of the family Zosimeidae Seifried, 2003 from Korean waters.